STUDY OF THE CONCEPT OF MOVEMENT DYNAMICS BASED ON ETHNOPHYSICS IN THE TANGGAI DANCE - Susiloningsih, Esti; Aslamiya, Putri Zasa; Fathurohman, Apit (Program Studi Pendidikan Fisika, FITK, UNSIQ, 2024)
Culture in Indonesia is known to be very diverse, which has not been explored to its full potential. There is a variety of knowledge in culture that many people do not know about. Local wisdom can be projected into learning at school. Physics learning is often still teacher centered with students becoming passive and feeling bored because they think this learning is only based on formulas. So local wisdom is needed with physics learning to implement the concept of movement dynamics with an ethnophysical approach by involving phenomena in students daily lives to more easily understand learning. Regional dances are one of the local wisdoms that have direct contact with students at school, one of which is the Palembang regional dance, namely the Tanggai dance. This research aims to identify studies of the concept of movement dynamics in movements in the Tanggai Palembang dance. This type of research uses descriptive qualitative with a documentation study approach and the object of this research is the Tanggai dance. Data was collected using two methods, namely the training video analysis method and literature study and the observation method. The results of the research obtained a study of the concept of movement dynamics in each of the Tangai Palembang dance movements, and learning through an ethnophysical approach has the potential to be an innovation in learning that can be applied in physics learning because it is able to train students' scientific literacy to think critically through culture that is integrated into knowledge.